2008
DOI: 10.1016/j.juro.2008.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Effect of a Somatostatin Analogue in Decreasing Mucus Production by the Intestinal Segment After Enterocystoplasty

Abstract: Sandostatin caused a marked decrease in mucus production by the intestinal segment with patients receiving Sandostatin no longer requiring routine postoperative bladder irrigation and having a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Of the included 20 studies, only 16 reported on our predefined primary outcomes. All studies were level of evidence 4 with one exception of a level 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included 20 studies, only 16 reported on our predefined primary outcomes. All studies were level of evidence 4 with one exception of a level 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 publications were included for the evidence synthesis after title, abstract and full text screening. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] 3.2 | Quality of the studies, risk-of-bias, and confounding assessment…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition, the dissolution of mucus can be promoted through the intravesical instillation of urea to disrupt the mucin molecule hydrogen bonds and to reduce the viscosity of mucin (5). Furthermore, a variety of agents, such as ethanol, formaldehyde, silver nitrate and octreotide, have been reported to reduce mucus secretion (6)(7)(8). Early mucus plug formation may also be prevented through the mechanical removal of intestinal mucosa (9), or through the use of an artificial bladder (10).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Subcutaneous octreotide has been shown to decrease mucus production through the inhibition of intestinal secretions. 20 Despite some promising results with each of these agents in small numbers of patients, there is currently no consensus on which agent is the most effective for reducing mucus-related problems after urinary diversion procedures.…”
Section: Overview Of Pharmacologic Optionsmentioning
confidence: 99%
“…In 2008, Khorrami et al 20 published the results of their placebocontrolled study of the use of octreotide to decrease mucus production after enterocystoplasty. Forty male patients were randomly assigned to receive either octreotide 50 mg or a placebo subcutaneously every 8 hours starting 1 hour before surgery and continuing for 15 days; patients discharged before the fifteenth day after surgery continued using octreotide but at a lower dosage (50 mg every 12 hours).…”
Section: Subcutaneous Octreotidementioning
confidence: 99%